Prácticas culturales en el cuidado prenatal: una exploración entre las mujeres indígenas del centro de salud Facundo Vela, septiembre-diciembre 2024. - Chiguano Cartagena, Tania Maribel (2025)
The research focuses on cultural practices related to prenatal care in indigenous women attended at the Facundo Vela Health Center, Ecuador, between September and December 2024. In a context where ancestral and western medicine coexist, the study seeks to understand how these practices influence prenatal care and the relationship with the health system. With the purpose of describing these practices through in-depth interviews, exploring experiences, beliefs and challenges lived during pregnancy and puerperium. A qualitative approach with phenomenological design was used, focusing on the deep understanding of the experiences of 10 indigenous women. Data collection was conducted through semi-structured interviews, and analysis was supported by Atlas.ti software to identify patterns and key themes. The results revealed that women employ traditional practices such as the use of medicinal plants, midwife massages and spiritual rituals, which reinforce their physical, emotional and cultural well-being. However, they also face barriers within the formal health system, such as discrimination, lack of cultural sensitivity and language difficulties, which affect confidence and access to services. In conclusion, integrating cultural practices into prenatal care could improve the quality of service and strengthen the relationship between indigenous women and health personnel. The importance of an intercultural approach that respects traditions and promotes more effective, inclusive and humanized care is highlighted